Shortage and famine in the late medieval Crown of Aragon - Franklin-Lyons, Adam, 1978- (Iberian encounter and exchange, 475-1755, 2022)
"Details the social causes and responses to three events of varying magnitude that struck the western Mediterranean: the minor food shortage of 1372, the serious but short-lived crisis of 1384-85, and the major famine of 1374-76, the worst famine of the century in the region. Shifts in military action, international competition, and violent attempts to control trade routes created systemic panic and widespread starvation--which in turn influenced decades of economic policy, social practices, and even the course of geopolitical conflicts. Providing new insights into the intersecting factors that led to famine in the fourteenth-century Mediterranean, this deeply researched, convincingly argued book presents tools and models that are broadly applicable to any historical study of vulnerabilities in the human food supply. It will be of interest to scholars of medieval Iberia and the medieval Mediterranean as well as to historians of food and of economics"--